Jewish Manuscript Cultures. New Perspectives - Wandrey, Irina (Studies in Manuscript Cultures, 2017)
Hebrew manuscripts are considered to be invaluable documents and artefacts of Jewish culture and history. Research on Hebrew manuscript culture is progressing rapidly and therefore its topics, methods and questions need to be enunciated and reflected upon. The case studies assembled in this volume explore various fields of research on Hebrew manuscripts. They show paradigmatically the current developments concerning codicology and palaeography, book forms like the scroll and codex, scribes and their writing material, patrons, collectors and censors, manuscript and book collections, illuminations and fragments, and, last but not least, new methods of material analysis applied to manuscripts. The principal focus of this volume is the material and intellectual history of Hebrew book cultures from antiquity to the Middle Ages and Early Modern Period, its intention being to heighten and sharpen the reader's understanding of Jewish social and cultural history in general.